Formação de biofilme por Rizobactérias isoladas de plantas do Semi-árido baiano - Barreto, Maira Merces (2009)
Bacteria occupy several niches in the environment, among them plant rhizosphere. Biofilms are microenvironments composed of microbial cells surrounded by an exopolysaccharide matrix (EPS). The nature and concentration of the nutrients available to bacteria influence biofilm structure, general characteristics and quantity of the produced EPS. The genera Pseudomonas, Bacillus and Alcaligenes are frequently found in soil and associated to plant roots. Where many species form biofilms establishing comensal, mutualistic or pathogenic interactions whit the plants. In our studies, biofilm production under different growth conditions by Gram positive and Gram negative bacteria isolated from the rhizosphere of Rupestrian Field plants of Bahia Semi-Arid region and their effects on tomato and lettuce plants. Were evaluated morphology of the colonies and molecular identification by 16S rRNA gene. Sequencing were performed. Biofilm was characterized micromorphologically and quantified in relation to different sugar types and concentrations. The biofilm produced showed diverse characteristics when bacteria were cultivated in different sugar trees ad concentrations. Isolates produced different amounts of EPS independing on the type and concentration of the monosaccharides used for growth. The Gram-positive isolate Rizo 35 cultivated on galactose at 6%, and the Gram-negative isolate Slim 04 grown o 6% glucose presented higher EPS production. None of the isolates promoted growth of tomato and lettuce in our experiments.